MODEL FOR PLANNING AN OPERATIONAL-INNOVATIVE PROGRAMME FOR AN INDUSTRIAL ORGANIZATION - Mezhov, Stepan; Lobaryov, Dmitriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The complex nature of modern technologies and organizational solutions in modern corporations requires adequate conceptual approaches to their planning. In this paper, the authors propose a model of an operational and innovative programme for which methodological principles are formulated and a systemic formulation of the planning task designed to optimize the process of resource use, including: investment, technological, and innovative capabilities of the corporation.In the instrumental sense, the task of forming a production programme must be based on optimization models. Some researchers supplement the models for calculating production programmes by analysing subsystems and forming the profile of economic risk.The purpose and essence of the proposed in this paper model of product planning in the context of continuous investment in innovation can be formulated as follows.On the basis of a number of parameters of the forecast cycle of production of each product of the production programme, it is necessary to determine such terms for launching new products in production in order to perform tasks regarding the rate of growth of the value of the corporation, to provide basic economic and financial indicators of efficiency and sustainability within the resources allocated by the corporate budget. At the same time, it is necessary to determine the optimal volumes and rates of investment in innovations, observing, on the one hand, the balance between profitability and liquidity, on the other hand, the optimal start date for the sale of a new product in order to maximize the rent from possessing unique competencies.